ANALISIS STRATEGI BADAN USAHA MILIK DESA (BUMDES) MUKTI TAMA DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DESA LAMBUR II KECAMATAN MUARA SABAK TIMUR - Mia Sumiati; Refnida; Hidayatul Arief (LPPM STAI Muhammadiyah Probolinggo, 2025)
Village-Owned Enterprises (BUMDes) play a strategic role in community economic empowerment through local potential management. This study aims to analyze the strategies implemented by BUMDes Mukti Tama in empowering the economy of Lambur II Village community, identify supporting and hindering factors, and formulate optimization steps. The research method uses a qualitative approach with case study, involving 4 informants selected through purposive sampling and snowball sampling techniques. Data collection techniques include non-participant observation, semi-structured interviews, and documentation. Data analysis uses the Miles and Huberman model with data source triangulation and member checking for validity. The results show that BUMDes Mukti Tama implements four main strategies: local potential-based through palm oil plantation management and palm oil trading, business diversification with tent rental and people's market, partnership with village government, and participatory approach to the community. Supporting factors include village government support, active participation of some community members, and adequate business facilities. Hindering factors include uneven community involvement, lack of effective socialization, and minimal youth involvement. Recommended optimization steps are strengthening communication with the community, conducting continuous program evaluation, and providing capacity development training. This research contributes to developing more effective and sustainable BUMDes strategies.